Sistem Usahatani Integrasi Tanaman Pangan dengan Kerbau Lumpur (Bubalus bubalus) di Kabupaten Brebes - Prasetyo Prasetyo; Muryanto Muryanto (Universitas Sebelas Maret (UNS), 2007)
The upland agro ecosystem wet climate and lowland agro ecosystem succulence on riverside that occur Brebes Regency potential for sector food plant and livestock development. The destination of survey for knows farming contribution buffalo into food plant farming system in upland and lowland agro ecosystem. The study application with survey method used questioner. The central livestock each village sample collected on district all over buffalo population. The based result debriefing to respondent know farming that application farmer largely is rice’s, corns, onions and buffalos. The Brebes Regency having wide rice’s land is 63.266 Ha. The feed capacities rice waste to livestock is 1.064.38,87 tons digested dry matter/livestock unit. The capacities corns waste to livestock is 78.386,01 tons digested dry matter/livestock unit and the capacities onions waste to livestock is 43.551,51 tons digested dry matter/livestock unit. The conclusion of study that buffalo breeding application as side effort (land plow, save, married child, house repaired) so that traditional bred management. The main farm is rice plants, corns and onion. The value of R/C ratio output more than one, farmer application farming system still reasonable for effort. The farming on lowland agro ecosystem big contribution in onions farm is 75,78%. At upland agro ecosystem big contribution in buffalo farm is 57,78%. Key words: integrated, food plants, buffalo, agroecosystem